Less aggressive disease in patients with primary squamous cell carcinomas of the thyroid gland and coexisting lymphocytic thyroiditis - Asik, Mehmet; Binnetoglu, Emine; Sen, Hacer; Gunes, Fahri; Muratli, Asli; Kankaya, Duygu; Uysal, Fatma; Sahin, Mustafa; Ukinc, Kubilay (Contemporary Oncology/Współczesna Onkologia, 2015)
Aim of the study : Primary squamous cell carcinoma (SCC) of the thyroid gland is extremely rare. Infrequently, primary SCC of the thyroid gland is accompanied by other thyroid diseases such as Hashimoto’s thyroiditis (HT). Recently, studies have demonstrated that differentiated thyroid cancer with coexisting HT has a better prognosis. However, the prognosis of patients with primary SCC of the thyroid gland and coexistent HT has not been clearly identified. We compared the clinical characteristics and disease stages of patients with primary SCC with and without lymphocytic thyroiditis (LT). Material and methods: We reviewed reports of primary SCC of the thyroid gland published in the English literature. Results and conclusions : We identified 46 papers that included 17 cases of primary SCC of the thyroid gland with LT and 77 cases of primary SCC of the thyroid gland without LT. Lymph node metastasis and local invasion rates did not differ between these two groups. Distant metastases were absent in patients with LT, and were observed in 13 (16.9%) patients without LT. A greater proportion of patients without LT had advanced stage disease (stage IV A-B-C) than patients with LT (p < 0.05). Patients with primary SCC of the thyroid gland and coexisting LT had lower tumour-node-metastasis stage and frequency of distant metastasis than those without LT. Lymphocytic infiltration in patients with SCC appears to limit tumour growth and distant metastases.